PENGARUH KUALITAS PELAYANAN DAN KEMUDAHAN PENGGGUNA TERHADAP KEPUASAN PELANGGAN GORIDE: (Studi Pada Konsumen Gojek di Kota Cirebon) - Mochamad Calvin Farell; Sudadi Pranata (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
The aim of this research is to determine the influence of service quality and ease of use on Goride customer satisfaction among Gojek users in Cirebon City. The research population includes all Goride users who use the Gojek application in Cirebon City, with a sample of 100 respondents. This research uses quantitative methods with purposive sampling through questionnaires. Data analysis was carried out using multiple linear regression with SmartPLS software. The research results show that service quality has a positive and significant effect on Goride customer satisfaction. Apart from that, ease of use also has a positive and significant impact on Goride customer satisfaction. Overall, service quality and ease of use have a positive and significant effect on Goride customer satisfaction among Gojek users in Cirebon City.